THE STABILITY OF IGNEOUS ANHYDRITE: EXPERIMENTAL RESULTS AND IMPLICATIONS FOR SULFUR BEHAVIOR IN THE 1982 EL CHICHON TRACHYANDESITE AND OTHER EVOLVED MAGMAS - Carroll Michael R.; Rutherford Malcolm J. (My University, 1987)
Hydrothermal experiments on natural samples of trachyandesite and dacite bulk composition show that anhydrite (CaSO4) may occur as a stable phenocryst phase at oxygen fugacities greater than or equal to 1.0 to 1.5 log fO2 units above the Ni-NiO equilibrium. The dissolved sulfur concentration in anhydrite saturated melts from MnO-Mn3O4 buffered experiments decreases with decreasing temperature, from approximately 2300 p.p.m.S at 1025°C to 250 p.p.m.S at 850°C (all at 2 kb Pfluid = Ptotal). In FeS-saturated melts equilibrated at the Ni-NiO buffer and 2 kb pressure, the concentration of dissolved sulfur also decreases with decreasing temperature, varying from approximately 400 p.p.m. S at 1025°C to less than 100 p.p.m. S at 850°C. At NNO or lowerfO2s, decreasing melt FeO content due to crystal fractionation may explain the observed decrease in sulfur solubility with decreasing temperature.Sulfur solubility values equivalent to the approximately 0.6 wt. per cent S present in fresh bulk pumice samples from the 1982 eruptions of El Chichon volcano are not readily achieved under any reasonable combinations of pressure, temperature, and oxidation state. Dissolved sulfur contents approaching 0.6 wt. per cent might occur if the source regions of melts parental to the El Chichon trachyandesite were at an fO2 several log units above the Ni-NiO equilibrium. Because such elevated oxidation states are far greater than the generally accepted values for mantle-derived partial melts we believe the high sulfur content of the El Chichon pumices is not a primary feature; it reflects reaction with sulfur enriched material at some unknown depth beneath the volcano. Published sulfur isotopic and petrologic data suggest that hydrothermally altered rocks similar to the pyrite- and anydritebearing lithic fragments found in the 1982 pumices could have provided a source of sulfur for crystallization of magmatic anhydrite. The anhydrite was an important source of sulfur for evolution of a sulfur-rich vapor phase during eruption of the magma.Although many calc-alkaline dacites and rhyolites appear to attain oxidation states high enough to stabilize anhydrite, the characteristically low bulk sulfur contents of these rocks will limit anhydrite abundances to less than approximately 0.1 wt. per cent, assuming sufficient sulfur is present to achieve saturation. Such small amounts of a water soluble mineral could be easily removed by subaerial weathering processes, dissolved during vapor exsolution from a magma, or simply overlooked during routine petrographic examination.